THERAPEUTIC USE OF ALPHA-LIPOIC ACID SUPPLEMENTATION: A REVIEW ON CURRENT USE AND FUTURE PROSPECTIVE - TAHA, MURTADA (International Journal of Applied Pharmaceutics, 2024)
Alpha-lipoic acid (ALA, thioctic acid, 5-(1,2-dithiolan-3-yl) pentanoic acid) is an organosulfur compound produced by plants, humans, and animals. ALA plays a crucial role in mitochondrial bioenergetics reactions. It is a natural antioxidant and a dithiol compound. ALA is a coenzyme that plays a crucial role in the function of pyruvate and Alpha-ketoglutarate dehydrogenase complexes found in mitochondria. ALA has cytotoxic and antiproliferative effects on several cancers, including Polycystic Ovarian Syndrome (PCOS). Most of ALA's clinical applications come from its antioxidant properties, but it also shows potential in treating female and male infertility. Although ALA can potentially be a therapeutic agent, its pharmacokinetic profile limits its effectiveness. Research suggests that ALA has a short half-life and low bioavailability (around 30%) because it gets broken down in the liver, has reduced solubility, and is unstable in the stomach. Liquid formulations have higher bioavailability and plasma concentration than solid dose forms. This review covers the current clinical evidence on using ALA to prevent, manage, and cure numerous disorders, including diabetic neuropathy, obesity, central nervous system-related ailments, and pregnancy abnormalities.